Early vs. interval approach to laparoscopic cholecystectomy for acute cholecystitis: a retrospective observational study from Pakistan - Raja, Sandesh; Ali, Azzam; Kumar, Dileep; Raja, Adarsh; Samo, Khursheed Ahmed; Memon, Amjad Siraj (Frontiers in Surgery, 2024)
BackgroundLaparoscopic cholecystectomy (LC) is the preferred treatment for acute cholecystitis (AC). However, the optimal timing for LC in AC management remains uncertain, with early cholecystectomy (EC) and interval cholecystectomy (IC) being two common approaches influenced by various factors.MethodsThis retrospective study, conducted at a tertiary care teaching hospital in Karachi, Pakistan, aimed to compare the outcomes of EC vs. IC for AC management. Patient data from January 2019 to September 2019 were analyzed with a focus on operative complications, duration of surgery, and postoperative hospital stay. The inclusion criteria were based on the Tokyo Guidelines, and patients underwent LC within 3 days of symptom onset in the EC group and after 6 weeks in the IC group.ResultsAmong 147 eligible patients, 100 underwent LC (50 in each group). No significant differences were observed in the sex distribution or mean age between the two groups. The EC group experienced fewer operative complications (12%) than the IC group (34%), with statistically significant differences observed. Nevertheless, no substantial variations in operative time or postoperative hospital stay were observed between the groups.ConclusionReduced complications in the EC group underscore its safety and efficacy. Nonetheless, further validation through multicenter studies is essential to substantiate these findings.